Estimating the Performance of Local Authorities as a Measure to Overpass the Financial Crisis: The Greek Case Study. Issue 14 (5th December 2016) - Askounis, Dimitrios; Ergazakis, Kostas; Mavri, Maria; Toska, Andry
ABSTRACT: Nowadays, local authorities face a number of problems that are related to the global economic crisis. For every government, the idea of measuring authorities' performances and transferring funds based on this estimation seems to be a solution for their sustainable development. In this article, we introduce a methodological framework for measuring the performance of local authorities based on the (a) quality of services offered, (b) complexity of operational procedures, and (c) cooperation with the central governance. Finally, we propose a model for improving local authorities' effectiveness.